Pengaruh Corporate Social Responsibility (CSR) dan Profitabilitas Terhadap Harga Saham pada Perusahaan yang Bergerak di Sub Sektor Produksi Batu Bara yang Terdaftar di BEI Tahun 2019-2022 - Nursam, Isnawati; Pakaya, Lukman; Panigoro, Nurharyati (Economic Reviews Journal, 2024)
This study aimed to determine the influence of Corporate Social Responsibility(CSR) and Profitability, measured by Return On Assets, on stock prices incompanies operating in the Coal Production Subsector listed on the IDX. Thisresearch was quantitative research. The population in this study was the coalindustry listed on the Indonesia Stock Exchange. The sample in this study wasobtained using purposive sampling, which is the selection of samples based onpredetermined criteria. Based on this technique, 11 samples were obtained from34 companies in the coal production subsector listed onthe Indonesia StockExchange during the 2019-2022 period. The method used was also panel dataregression analysis using the SPSS program. The results of this study indicate that(1) corporate social responsibility (CSR) has a positive and significant influenceon stock prices, (2) company profitability has no significant influence on stockprices, (3) simultaneously, corporate social responsibility (CSR) and profitabilityhave a positive and significant influence on stock prices of companies operating inthe Coal Production Subsector, with a coefficient of determination of 0.917.Thisfigure indicates that Corporate Social Responsibility and profitability explainapproximately 91.7% of the variation in stock prices of companies in the coalproduction subsector listed on the Indonesia Stock Exchange (IDX) during the2019-2022 period. Meanwhile, the influence of other variables on stock pricesis8.3%, which includes other fundamental and technical factors.Keywords: Corporate Social Responsibility (CSR),Profitability,Stock Prices.